Pyoderma Gangrenosum in a Patient with Crohn’s Disease Treated with Adalimumab: A Case-Based Review and Systematic Review of the Current Literature - Fotios S. Fousekis; Konstantinos Mpakogiannis; Emmanouil Karampinis; Ioanna Nefeli Mastorogianni; Dimitrios K. Christodoulou; Marina Papoutsaki; Evanthia Zampeli; Konstantinos H. Katsanos (Clinics and Practice)
Background: Pyoderma gangrenosum (PG) is a rare inflammatory cutaneous disorder that frequently occurs in association with systemic diseases such as inflammatory bowel disease (IBD). This case report describes a 23-year-old female with Crohn’s disease (CD) who developed PG and was successfully treated with adalimumab. The objective of this study is to present the clinical course, treatment approach, and outcomes while reviewing the existing literature on the efficacy of adalimumab in PG management. Methods: A case report is presented, detailing clinical presentation, diagnostic evaluation, and treatment strategy. Additionally, a systematic review was conducted using PubMed to assess studies on adalimumab in PG, focusing on treatment response, remission rates, and adverse effects. Results: The patient presented with ulcerative lesions on her lower extremities and sacroiliitis. After corticosteroid therapy, adalimumab was initiated, leading to significant ulcer healing, reduced back pain, and CD remission. The systematic review identified seven studies on adalimumab in PG. Findings suggest that adalimumab is effective in steroid-refractory cases, with remission achieved in a significant proportion of patients. The most common adverse effects were infections, but overall, adalimumab showed a favorable safety profile. Conclusions: This case highlights the importance of early diagnosis and multidisciplinary management of PG in CD patients. Adalimumab appears to be a promising therapeutic option, particularly for steroid-resistant PG, though further research is needed to establish standardized treatment protocols.